Revisiting Gender Equality in the Qur’an: A Contextual Reading of Nasaruddin Umar’s Thought - Nur Rofi'ah (IJMIS: Istiqlal Journal on Mosque and Islamic Studies, 2024)
The book Argumen Kesetaraan Jender Perspektif Al-Qur’an by Nasaruddin Umar stands as one of the most influential works in contemporary Islamic discourse in Indonesia, particularly in the field of Qur’anic exegesis from a gender equality perspective. Originating from the author’s doctoral dissertation in Qur’anic studies, this work not only offers a rigorous academic analysis but also proposes a new intellectual framework capable of bridging sacred texts with modern social dynamics. In the context of growing global awareness of gender justice, this book remains highly relevant and continues to serve as a key reference for interpreting the Qur’an in a manner that is just, contextual, and humanistic.